Introduction to Permanent Plug and Abandonment of Wells - Khalifeh, Mahmoud; Saasen, Arild (Ocean Engineering & Oceanography, 2020)
This open access book offers a timely guide to challenges and current practices to permanently plug and abandon hydrocarbon wells. With a focus on offshore North Sea, it analyzes the process of plug and abandonment of hydrocarbon wells through the establishment of permanent well barriers. It provides the reader with extensive knowledge on the type of barriers, their functioning and verification. It then discusses plug and abandonment methodologies, analyzing different types of permanent plugging materials. Last, it describes some tests for verifying the integrity and functionality of installed permanent barriers. The book offers a comprehensive reference guide to well plugging and abandonment (P&A) and well integrity testing. The book also presents new technologies that have been proposed to be used in plugging and abandoning of wells, which might be game-changing technologies, but they are still in laboratory or testing level. Given its scope, it addresses students and researchersin both academia and industry. It also provides information for engineers who work in petroleum industry and should be familiarized with P&A of hydrocarbon wells to reduce the time of P&A by considering it during well planning and construction.